Social Media and Academic Excellence (Journal of the College of Education for Women, 2020)
The current research seeks to shed light on the role that social media can play, through the optimal use of it by students, in achieving academic excellence. The most prominent aims that constitute it are:Identifying the social sites most used by students; learning how students interact with the published study material on communication sites and benefit from them to achieve their academic excellence; and knowing the connection between using social media and achieving academic excellence, and the role that these sites play in achieving academic excellence.That incorrect use by students leads to adverse results, and thus affects their academic level. Failure of parents to monitor their student’ use of social media leads to the lack of benefit from them in achieving academic excellence. This means the lack of procetures for monitoring these networks makes them more harmful for Students. Moreover, the excessive use of social media by students has a negative impact on the student’s performance of his homework. It has negative effects on his health as well. In light of the results reached, the researchers presented a set of recommendations, including:Parents should ensure that their children use social media as a tool to improve their children's educational level. Students should better manage their study time and prevent distortions that social media can provide. Students must strike a balance between using the means of communication and their study duties in a way that does not affect their studies. Students, during their use of social media, focus on the scientific importance of these sites instead of using them entertainment.